Faktor-Faktor Konversi BTA Penderita Tuberkulosis Paru Di Rumah Sakit Umum Haji Medan - Ayunda Pratiwi L. Tobing; Ance Roslina (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2021)
Background : Pulmonary tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis. Some of the risk factors for pulmonary TB disease include age, sex, history of OAT, comorbidities such as DM and HIV and cigarette and alcohol consumption. Sputum culture examination is the gold standard used in monitoring treatment in TB patients. Evaluation of AFB conversion from positive to negative from the bacterium Mycobacterium tuberculosis is an important indicator for monitoring treatment in TB patients. Objective : To determine the factors that influence the BTA conversion of pulmonary tuberculosis patients in Haji Medan General Hospital. Methods : The study was a descriptive study with cross sectional approach and collecting medical records, this study was conducted in January 2018 - November 2019 with a sample of 71. Results : The results showed that the most smear conversion occurred at the age of 20-29 years, 50.7% were female, 70.4% had no history of accompanying DM, 94.4% had no history of HIV comorbidities, 100% had no previous OAT history , 72.4% did not smoke, and 86.2% did not consume alcohol. Conclusion : AFB conversion occurs mostly at a young age, female sex, no history of DM and HIV, no history of OAT, no smoking and alcohol use.